Effects of Improved DNA Integrity by Punch From Tissue Blocks as Compared to Pinpoint Extraction From Unstained Slides on Next-Generation Sequencing Quality Metrics. Issue 1 (20th March 2019) - Morlote, Diana; Janowski, Karen M; Siniard, Rance C; Guo, Rong Jun; Winokur, Thomas; DeFrank, Gina; Harada, Shuko
ABSTRACT: Objectives: To compare the effects of two methods of formalin-fixed paraffin-embedded (FFPE) tissue harvesting on DNA quality and next-generation sequencing (NGS) quality metrics. Methods: DNA integrity number (DIN) and NGS quality metrics resulting from DNA extraction and sequencing of 199 sequential samples harvested via the Pinpoint Slide DNA Isolation System and the punch method were compared. Results: DNA extracted from FFPE tissue punches had higher DIN than that extracted from Pinpoint samples (mean ± SD, 6.18 ± 0.83 vs 5.09 ± 0.91; P < .0001), indicating less degradation. Lower DIN correlated with lower-quality metrics of NGS, that is lower percentage of unique on-target reads, average depth of coverage, and percentage of positions with coverage depth greater than or equal to 100×, 400×, and 1, 000×. Conclusions: Our study demonstrated methods to harvest tissue from FFPE blocks may affect quality of DNA, which in turn has an effect on other NGS quality metrics.